138 Catheter ablation of atrial fibrillation whilst taking therapeutic warfarin: a british experience. (22nd September 2015) - Makosch, G A; Griffiths, A; Meredith, T; Qureshi, N; Wong, K; de Bono, J; Bashir, Y; Betts, T R; Rajappan, K
Abstract : Introduction: Peri-procedural anticoagulation of patients undergoing catheter ablation of atrial fibrillation (AF) reduces thromboembolism risk but with potential haemorrhagic complications. In the UK, warfarin is generally discontinued pre-procedure and low molecular weight heparin (LMWH) used to bridge the sub-therapeutic period. In some institutions around the world ablation is performed with a therapeutic International Normalised Ratio (INR) and problems with LMWH administration are reduced, but the trans-septal puncture is usually performed under intracardiac echo (ICE) guidance. In the UK, cost prevents routine ICE use but we aimed to see if this could still be done safely within our system. Methods: Fifty-six consecutive AF ablation patients were studied prospectively (warfarin group). A target INR of 2–3 was used for the procedure. A double trans-septal puncture technique was used. Unfractionated heparin was still used to maintain ACT between 300 and 350. Wide area circumferential ablation was performed along with any other ablation clinically indicated. If the INR was less than two at the time of ablation, LMWH was used afterwards until it was two or more. A group of 56 patients prior (bridging LMWH group) were compared. Endpoints were minor bleeding (haematomas), major bleeding (transfusion requiring), pericardial effusions, and stroke. Results: In two patients the INR was >3 so the procedure was delayed. In 11 the INR was <2. In 43 the INR was 2–3 and they were all successfully ablated. The endpoint results are shown in the Abstract 138 table 1 . The patient who had a pericardial effusion and tamponade during the procedure had ablation completed after reversal of the heparin and drainage, and warfarin was omitted for 24 h only. There were no pseudoaneurysms in the warfarin group and one in the bridging LMWH group. Conclusions: AF ablation can be performed safely with therapeutic warfarin in the UK, with a low rate of procedure cancellation. Although the number of patients studied was relatively small, there was a lower incidence of minor bleeding with this approach than with bridging LMWH and a low rate of other complications in both groups. This strategy also reduces the need for LMWH after ablation which has both cost and patient comfort implications.